Survival of maxillary and mandibular bonded retainers 10 to 15 years after orthodontic treatment: a retrospective observational study - Katharina E. Kocher; Meret C. Gebistorf; Nikolaos Pandis; Piotr S. Fudalej; Christos Katsaros (SpringerOpen, 2019)
Abstract Background The long-term evidence regarding failures of fixed retainers is limited and the aim of this cohort study was to assess the long-term risk of failure of one type of maxillary and two types of mandibular fixed lingual retainers. Trial design Retrospective cohort study. Methods Eighty-eight patients in retention 10-15 years after orthodontic treatment were included. The type of failure; number of failures per tooth, per patient, and retainer; and adverse effects were assessed by (1) a questionnaire, (2) clinical examination, and (3) screening patients' clinical charts. Descriptive statistics were calculated and a Cox regression was used to assess possible predictors for mandibular retainer survival. Results and conclusions In the mandible, 47 (53.4%) .016" × .022" braided stainless steel retainers (SS) were bonded to all six anterior teeth, and 41 (46.6%) .027" β-titanium (TMA) retainers were bonded to the canines only. From the SS retainers 40.4% and of the TMA retainers 61% had no failures during the whole observation period. SS failures per retainer were 2.17 (3.15) vs. 0.66 (1.03) for TMA. The type of retainer was the only significant predictor for failure. In the maxilla, 82 (93.2%) .016" × .022" braided SS retainers were bonded to all four incisors and six retainers (6.8%) to all six anterior teeth. The latter group was not further analyzed due to the small sample size. From the retainers bonded to all four incisors, 74.4% had no failure during the whole observation period. SS average number of failures per retainer bonded to the four incisors was 1.14 (SD 2.93). Overall, detachments were the most frequent type of first failure followed by composite damage. From the original mandibular retainers 98.9% and of the original maxillary retainers 97.6% were still in situ 10-15 years after debonding. No adverse torque changes were observed. Limitations Potential effects of selection bias, information bias, and attrition bias as well as possible confounding factors cannot be fully excluded in this study.